The Key Role and Mechanism of Oxidative Stress in Hypertrophic Cardiomyopathy: A Systematic Exploration Based on Multi-Omics Analysis and Experimental Validation - Sijie Zhang; Tianzhi Li; Shiyi Sun; Yujiao Jiang; Yuxin Sun; Yan Meng (Antioxidants)
Hypertrophic cardiomyopathy (HCM), characterised by abnormal ventricular thickening, involves complex mechanisms including gene mutations, calcium dysregulation, mitochondrial dysfunction, and oxidative stress. Oxidative stress plays a pivotal role in the progression of HCM by mediating cardiomyocyte injury and remodelling. This study systematically analysed HCM transcriptomic data using differential gene expression, weighted gene co-expression network analysis (WGCNA), and unsupervised consensus clustering to identify key genes and classify HCM subtypes. Four oxidative stress-related characteristic genes (DUSP1, CCND1, STAT3, and THBS1) were identified using LASSO regression, SVM-RFE, and Random Forest algorithms. Their functional significance was validated by immune infiltration analysis, drug prediction using the cMAP database, and molecular docking. Single-cell RNA sequencing revealed their cell-type-specific expression, and in vitro experiments confirmed their role in HCM. These findings provide insights into oxidative stress mechanisms and potential therapeutic targets for HCM.